2020
DOI: 10.3390/math8040646
|View full text |Cite
|
Sign up to set email alerts
|

An AHPSort II Based Analysis of the Inequality Reduction within European Union

Abstract: Nowadays, sustainability is an omnipresent concept in our society, which encompasses several challenges related to poverty, inequality, climate change and so on. The United Nations adopted the Agenda 2030, a plan of action formed of universal Sustainable Developments Goals (SDGs) and targets, which countries have to face in order to shift the world toward a sustainable future. One of the most relevant SDGs since the onset of the financial crisis in 2007 has been the so-called reduced inequalities, which consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…As an extension of the AHPSort method, AHPSort II has fewer comparison times, more convenient usage, more accurate results, and its effectiveness has been verified ( Xie et al, 2019 ). Labella et al (2020) used AHPSort II to assess the performance of EU countries to reduce inequality. Xu et al (2019) combined interval type-2 fuzzy sets (IT2FSs) with AHPSort II to show a new supply chain management method, which is proved to have higher priority accuracy than traditional methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As an extension of the AHPSort method, AHPSort II has fewer comparison times, more convenient usage, more accurate results, and its effectiveness has been verified ( Xie et al, 2019 ). Labella et al (2020) used AHPSort II to assess the performance of EU countries to reduce inequality. Xu et al (2019) combined interval type-2 fuzzy sets (IT2FSs) with AHPSort II to show a new supply chain management method, which is proved to have higher priority accuracy than traditional methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their evaluation showed that the proposed mixed strategy portfolio for green aviation fleet management could be determined using limited resources. Some authors concentrated their efforts on selecting or ranking strategies to make the infrastructure sector more sustainable [81,87,[89][90][91][92][93][94].…”
Section: Sdg 9: Industry Innovation and Infrastructurementioning
confidence: 99%
“…Table 9 presents the contributions of MCDM methods related to this category [94,95]. Labella et al [94] developed a novel approach to evaluate the inequalities in the European Union (EU) countries based on a compromise method (AHPSort II).…”
Section: Sdg 10: Reduced Inequalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In an international context, the literature on growth and convergence is extensive [26][27][28][29][30][31][32][33][34][35]. According to Willington [36], following Baumol [23], empirical evidence on this subject has expanded rapidly, with new criticisms emerging, both theoretical and empirical, while proposing new alternative estimation methods.…”
Section: Subsectionmentioning
confidence: 99%